Trends of Development of Civic Organizations in Modern Ukraine - Yevdokymova, Iryna; Vitkovska, Inna (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
The article is devoted to analysis of the trends of formation of civic organizations in Ukraine as an element of civil society and as a catalyst for its development. In the article the results of statistical and sociological empirical studies that were held in Ukraine since 2014 by State Statistics Service of Ukraine, Ilko Kucheriv Democratic Initiatives Foundation (DIF), Ukrainian Center for Economic and Political Studies O. Razumkov, Kyiv International Institute of Sociology, European Research Association (ERA) and research center GfK-Ukraine are analyzed. The authors of the article analyzed the data on the number of registered civic organizations, the main directions of their activities, sources of funding, participation of citizens in their activities, the level of trust to civic organizations from the population in order to distinguish the main trends of the development of civic organizations in Ukraine. Based on the secondary analysis of the results of empirical sociological and statistical studies, the article outlines the main trends in development of civic organizations in Ukraine such as: growing of registered civic organizations number; increasing in number of organizations that are focused on solving the problems of servicemen, internally displaced persons and citizens affected by the conflict in eastern Ukraine; increasing in funding of civic organizations mainly by means of revenues from international charity donors; spreading of practices of volunteer activity among Ukrainian population; growing the level of  trust  among  Ukrainian population to volunteer activity and to civic organizations etc.